Melasma in Orientals - Apichati Sivayathorn (2018)
Melasma is an acquired hyperpigmentary disorder commonly seen in Orientals. The pattern of pigmentary change in this condition is very characteristic and the diagnosis is usually evident to the patient. A number of pigmentary disorders mimicking melasma have been reported in Asian people. They include Riehl’s melanosis, pigmented actinic lichen planus, and acquired bilateral naevus of Otalike macules. Increased awareness of these pigmentary disorders should lead to the correct diagnosis. Data on the prevalence of melasma are very limited. In South East Asia, melasma accounts for 0.25 to 4% of patients seen in dermatology institutes, with peak incidence in those aged 30 to 44 years. The disorder is seen much more commonly in females than in males. Although the general prevalence of this condition in the population is not known, one simple survey suggests that the prevalence of melasma may be as high as 40% in females and 20% in males. Multiple causative factors have been implicated in the aetiology of melasma; of these, sunlight appears to be the most important in causing and aggravating the condition in susceptible individuals. Genetic factors are also important: in many studies, 20 to 70% of patients reported having close relatives who were similarly affected. In about 10 to 20% of patients with melasma, the use of contraceptive pills has been implicated as the cause of this disorder. Adverse effects resulting from self-medication and treatments offered by beauticians are frequently encountered. Treatments provided by dermatologists are generally safer and much more effective. The mainstay of treatment is the proper use of safe depigmenting agents. Additional measures such as avoidance of sunlight are important for achieving good therapeutic results. © 1995, Adis International Limited. All rights reserved.